2016
DOI: 10.1371/journal.ppat.1005748
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus Immediate-Early 1 Protein Rewires Upstream STAT3 to Downstream STAT1 Signaling Switching an IL6-Type to an IFNγ-Like Response

Abstract: The human cytomegalovirus (hCMV) major immediate-early 1 protein (IE1) is best known for activating transcription to facilitate viral replication. Here we present transcriptome data indicating that IE1 is as significant a repressor as it is an activator of host gene expression. Human cells induced to express IE1 exhibit global repression of IL6- and oncostatin M-responsive STAT3 target genes. This repression is followed by STAT1 phosphorylation and activation of STAT1 target genes normally induced by IFNγ. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 176 publications
4
59
0
Order By: Relevance
“…However, due to STAT1's well-established role in antiviral responses, the activation of STAT1 could potentially be a double-edged sword in that it promotes proviral monocyte biological changes but may also inhibit viral replication. This is illustrated in a study by Harwardt et al, in which the virus rewires STAT signaling in infected fibroblasts (103). In this study, HCMV IE1 binds to STAT3, depleting cytoplasmic stores of STAT3 that would become activated by JAK kinases following IFN signaling.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…However, due to STAT1's well-established role in antiviral responses, the activation of STAT1 could potentially be a double-edged sword in that it promotes proviral monocyte biological changes but may also inhibit viral replication. This is illustrated in a study by Harwardt et al, in which the virus rewires STAT signaling in infected fibroblasts (103). In this study, HCMV IE1 binds to STAT3, depleting cytoplasmic stores of STAT3 that would become activated by JAK kinases following IFN signaling.…”
Section: Discussionmentioning
confidence: 67%
“…4C and E to G), rather than the traditional IFN-dependent pathway (Fig. 3) or the IE-induced rewiring of JAK/STAT signaling (103). Perhaps this unique regulation of STAT1 activation helps to overcome the hurdle of STAT1's potential antiviral activity while helping to regulate monocyte motility and differentiation.…”
Section: Discussionmentioning
confidence: 96%
“…The US12 family targets pro-inflammatory mediators, such as multiple members of the tumour necrosis factor receptor (TNFR) superfamily (TNFRSF8, TNFRSF12A, NGFR, LTBR), gp130 (IL6ST), the IL-6 receptor signaling receptor, pannexin-1 (PANX1) and the TLR4 ligand high-mobility group protein B1 (HMGB1) (Croft et al, 2013; Kanneganti et al, 2007; Park et al, 2004). IL6ST signaling may also have antiviral effects in the context of HCMV (Harwardt et al, 2016), which was suggested by the finding that disruption of gp130 STAT3 binding resulted in IFN-like signaling through STAT1(Costa-Pereira et al, 2002). …”
Section: Discussionmentioning
confidence: 99%
“…IFNγ inhibits the infection of cytomegalovirus, while IL18 can facilitate the secretion of IFNγ to control virus infections [21, 22]. Although IL10 is usually considered to be a suppressor for host immunity, it actually has a complicated role in MCMV infection [23, 24].…”
Section: Resultsmentioning
confidence: 99%
“…IFNγ can inhibit HCMV infection by regulating the expression of immediate early genes [21, 34]. The similar function of IFNγ also works in the process of MCMV infection [35, 36].…”
Section: Discussionmentioning
confidence: 99%